The Wall Street MBA : your personal crash course in corporate finance - Advani, Reuben (McGraw-Hill Education, 2018)
Mastering corporate finance is a lot easier than you think. Business school textbooks are notoriously dry, static, and filled with confusing acronyms. The Wall Street MBA takes a different approach by presenting a succinct "crash course," breaking down the main concepts of MBA finance and accounting programs to provide the information and insight you need to: " eview financial statements " nalyze earnings " etect fraud " alue companies " etermine the cost of capital Fully updated and revised, this new edition will also get you up to speed on important new trends in FinTech, alternative investments, and cost accounting. This highly accessible ground-floor view of corporate accounting offers everything you need to navigate today's financial landscape with the knowledge and confidence of a seasoned pro